A stochastic differential equation approach to the analysis of the UK 2016 EU referendum polls. (22nd May 2018) - Fenner, Trevor; Levene, Mark; Loizou, George
Abstract: Human dynamics and sociophysics suggest statistical models that may explain and provide us with better insight into social phenomena. Here we propose a generative model based on a stochastic differential equation that allows us to analyse the polls leading up to the UK 2016 EU referendum. After a preliminary analysis of the time series of poll results, we provide empirical evidence that the beta distribution, which is a natural choice when modelling proportions, fits the marginal distribution of this time series. We also provide evidence of the predictive power of the proposed model.